High content analysis of sea buckthorn, black chokeberry, red and white currants microbiota - A pilot study - Lukša, Juliana; Vepštaitė-Monstavičė, Iglė; Yurchenko, Vyacheslav; Serva, Saulius; Servienė, Elena (Food research international, 2018)
The high potential of sea buckthorn, black chokeberry, red and white currants in healthy food industry boosted interest in the plant cultivation. The present study is the first work providing comprehensive information on microbial populations of these berries. Next Generation Sequencing allowed identification of eukaryotic and prokaryotic microorganisms prevalent on specific berries, including uncultivable microorganisms. Our study revealed the broad diversity of berries-associated bacterial and fungal microorganisms. Analysis of representative microbial OTUs showed a clear separation among inhabitants of sea buckthorn, black chokeberry and both currants, indicating plant-defined differences in the composition of the bacterial and fungal microbiota. Among the microorganisms distributed on tested berries, we documented potentially beneficial fungi and bacteria along with potential phytopathogens or those harmful for humans. Thus, plant microbiota appears to be highly relevant for the evaluation of the microbiota impact on food quality and human health.
Keywords: DNA fungální; DNA, Fungal; Food Quality; DNA bakterií; Humans; Fungi; potravinářský průmysl; mikrobiota; houby; Hippophae; Microbiota; lidé; Photinia; pilotní projekty; Pilot Projects; Lithuania; DNA, Bacterial; Litva; biodiverzita; ovoce; kvalita jídla; Fruit; Bacteria; Ribes; Food Industry; Biodiversity